Transfusing the essence of a city designing a community market diffusing downtown Sorsogon's congestion and reconnecting the community of Sirangan - Carreon, Aries Angelo D.; Espina, Mary Ann A. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Sorsogon City is the administrative, educational, and commercial center of Sorsogon province. Located at the bottommost part of Luzon, it is the transshipment corridor from the island of Luzon to Visayas. These factors contribute to the progress and economic advance of the city ; evidence of increasing commercial establishment in the downtown area of the city are prominent. Alongside the economic development of Sorsogon is the urbanization of the city. Looking inside the city center are sporadic erection of business establishments in the cramped commercial zone creating unwanted congestion, and the area of Sirangan, despite the space it has, doesn't have any commercial structure, making it a habitat for informal settlers. in the design of a new building housing commercial spaces in the area of Sirangan, and providing a spaces of culture and people activities, the life of the city can be transmitted to its other parts making a holistic urbanization. Tapping onto the humanistic approach to architecture can create the solution for problems existing in the urban environment.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman